An Analysis of English Assessments for Deaf Students at SLB Negeri 1 Buleleng - Pusparani, Ni Ketut Indah (STKIP AGAMA HINDU SINGARAJA, 2024)
Teaching English to students with hearing loss is complex due to their reliance on non-auditory communication methods such as gestures, sign language, body language, and facial expressions. Deaf learners often have limited vocabulary, creating a language barrier with hearing students. This study examines how the assessments are conducted to gauge deaf students' learning English process at SLB Negeri 1 Buleleng. This study is classified as a case study conducted using qualitative methods. The data were taken from an interview and observation of the English Teacher in SLB Negeri 1 Buleleng. The findings reveal that the assessments include formative methods, such as vocabulary memorization and presentation, and summative methods, such as multiple-choice questions with visual aids.